The Effect of Osteoporosis on Postoperative Outcomes Following Total Ankle Arthroplasty - Ronit Kulkarni BS; Joshua L. Morningstar BS; Richard J. Friedman MD, FRCSC; Christopher E. Gross MD; Daniel J. Scott MBA, MD (Foot & Ankle Orthopaedics)
Category: Ankle; Ankle Arthritis Introduction/Purpose: Recent literature, particularly in the fields of total joint arthroplasty, has raised concern for increased perioperative complications following joint arthroplasty in patients with osteoporosis. The purpose of this study is to evaluate the influence of preoperative osteoporosis on 6-month postoperative outcomes following total ankle arthroplasty (TAA). Methods: The Nationwide Readmissions Database (NRD) was queried from 2015-2020 to identify 29,705 patients undergoing primary elective TAA. Patients were divided into two cohorts based on the presence of preoperative osteoporosis (as defined by ICD-10 CM codes M81, M80, M80.07XX), with 943 (3.3%) having this diagnosis. Preoperative demographics, comorbidities, postoperative outcomes, cost of admission, and total length of stay (LOS) were analyzed between cohorts. Multivariate regression analyses were conducted to control for predictors of adverse postoperative outcomes other than preoperative osteoporosis. Results: The overall cohort was majority male (54.2%) with mean age of 64.15 (range 17-90) years, and Charlson-Deyo Comorbidity Index (CCI) score of 0.65 (range 0-12). Patients diagnosed with preoperative osteoporosis patients were statistically significantly older (Osteoporosis=68.72 years; non-osteoporosis=65.03 years; p<.001), more likely to have Medicare insurance (p<.001), and had a higher CCI score (Osteoporosis=0.98; Non-Osteoporosis=0.64; p<.001). Multivariate regression analysis of 180-day postoperative outcomes found that preoperative osteoporosis was significantly predictive of increased risk of any complication (OR=1.428; p<.001), transfusion (OR=3.370; p<.001), pulmonary embolism (OR=5.625; p=.016), Pneumonia (OR=3.872; p<.001), adverse discharge (OR=1.445; p<.001), and extended stay greater than 4 days (OR=1.310; p<.001). Further, the presence of osteoporosis is predictive of nearly a $3,000 increase in total cost of procedure (β= 2980.22; p<.001). Conclusion: The presence of osteoporosis was significantly predictive of higher rates of postoperative complications, LOS, and a substantially higher cost of procedure following TAA. Physicians and patients alike should consider this comorbidity when stratifying risk for outcomes following total ankle arthroplasty.